2018
DOI: 10.1186/s13071-018-3226-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of the Aedes aegypti (Diptera: Culicidae) mosquito in El Salvador, vector of dengue, yellow fever, chikungunya and Zika

Abstract: BackgroundAedes aegypti is associated with dengue, yellow fever, chikungunya and Zika viruses. This vector is widespread in tropical and subtropical areas, and can also occur in temperate areas at higher latitudes. The geographical distribution of Ae. aegypti continues to spread due to human activities. This is the first study to examine the population genetic structure of this insect in El Salvador, Central America.MethodsAedes aegypti larvae were collected from six geographical regions of El Salvador: Sonson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 43 publications
4
24
0
Order By: Relevance
“…The overall haplotype diversity detected in this study was similar to what could be found elsewhere (Calvez et al., 2016; Joyce, Torres, Torres, & Moreno, 2018; Liu et al., 2019). This could be attributed to the fact that these mosquitoes are migrating a lot.…”
Section: Discussionsupporting
confidence: 91%
“…The overall haplotype diversity detected in this study was similar to what could be found elsewhere (Calvez et al., 2016; Joyce, Torres, Torres, & Moreno, 2018; Liu et al., 2019). This could be attributed to the fact that these mosquitoes are migrating a lot.…”
Section: Discussionsupporting
confidence: 91%
“…aegypti to be evaluated for vector control applications [ 42 46 ]. Aedes aegypti is widespread in tropical and subtropical regions globally [ 47 , 48 ], and since its detection in California in 2011 it has become widespread in southern California and the Central Valley [ 49 , 50 ]. One example of where Wolbachia -infected Ae .…”
Section: Introductionmentioning
confidence: 99%
“…PCR reactions were performed in a final volume of 20 µL containing 10 µL qScript TM One-Step, Low ROX TM (Quantabio, Carlsbad, CA, United States), 10 µM of each primer and 5 µL of RNA. The primers LCO1490 (5 -GGT CAA ATC ATA AAG ATA TTG G-3) and HCO2198 (5 -TAA ACT TCA GGG TGA CCA AAA AAT CA-3 ) were also used (Joyce et al, 2018). The thermal profile consisted of the following: one cycle at 50 • C for reverse transcriptase activation for 10 min followed by initial denaturation at 95 • C for 1 min, 45 cycles of 94 • C for 10 s, 60 • C for 1 min and final extension at 72 • C for 10 min.…”
Section: Morphological and Molecular Identification Of Aedes Speciesmentioning
confidence: 99%
“…This tool uses a small fragment of DNA which functions as a specific barcode for each species. In insects, this fragment corresponds to a sequence of ∼ 650 base pairs (bp) located at the 5 end of the cytochrome c oxidase subunit I gene (COI) (Joyce et al, 2018). Therefore, it is important to conduct molecular identification of species using barcoding to accurately identify individuals.…”
Section: Introductionmentioning
confidence: 99%